Teaching in the name of justice: empathy and vulnerability as a basis for understanding difficult histories. (20th October 2022) - Harrison, Neil; Stanton, Sue; Manning, Richard; Penetito, Wally
ABSTRACT: In this article, two autoethnographies from Australia and New Zealand provide a means of engaging students in difficult histories of colonial nations. The first looks to knowledge as a basis of understanding others, and the second focuses on concepts of empathy and vulnerability as a way of understanding difficult histories. Each of these autoethnographies are accompanied by collaborative writing, where the authors come together to reflect on these narratives through the frame of sociocultural theory. We propose a notion of empathy as enacted, rather than as an attribute that someone has in order to bring things closer. Rather than being governed by proximity, empathy can be performative in reconfiguring an interaction between narratives and memories. It is time for history education in colonial countries to reflect on the reproduction of its own theory of reason, and to move beyond its own existence as a colonial enterprise. The collaboration central to this article reflects the shared purpose of teaching in the name of justice.